1999
DOI: 10.2136/sssaj1999.634987x
|View full text |Cite
|
Sign up to set email alerts
|

Field Calibration of a Capacitance Water Content Probe in Fine Sand Soils

Abstract: Fine sand soils important to Florida agriculture have volumetric soil water content values (θv) of <0.10 cm3 cm−3 after drainage due to gravity has ceased. Small changes in θv in the range of 0.02 to 0.08 cm3 cm−3 can greatly affect plant available water and, therefore, good calibration of soil water content sensors is necessary. The EnviroSCAN (Sentek Pty. Ltd., South Australia) is a multiple sensor capacitance probe capable of continuous measurement of soil water content by volume (θv). Many fine sand soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
44
1
15

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 1 publication
1
44
1
15
Order By: Relevance
“…Calibrations for specific soils have also been reported by others, including Mead et al (1995) for sandy loam, Paltineanu and Starr (1997) for silt loam, and Morgan et al (1999) for fine sand; however, the validity of manufacturer's calibration has not been demonstrated for coarse-textured soils. Gardner et al (1998) and Gupta and Jangid (2011) found that for a given u v a greater bulk density (r b ) results in a larger relative dielectric permittivity (K a ) (commonly referred to as dielectric constant) than a lower density.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…Calibrations for specific soils have also been reported by others, including Mead et al (1995) for sandy loam, Paltineanu and Starr (1997) for silt loam, and Morgan et al (1999) for fine sand; however, the validity of manufacturer's calibration has not been demonstrated for coarse-textured soils. Gardner et al (1998) and Gupta and Jangid (2011) found that for a given u v a greater bulk density (r b ) results in a larger relative dielectric permittivity (K a ) (commonly referred to as dielectric constant) than a lower density.…”
mentioning
confidence: 60%
“…Multiple capacitance sensors can be placed on a single probe, with the number and spacing of sensors set by the user. Sensor reading-time intervals are also flexible and can be set by the user to vary from 1 min to 6.9 d. The accuracy of these sensors can be affected by: uncontrolled humidity inside the access tubes, air gaps around the tubes caused by poor field installation, positional changes in orientation within the tube, and alteration of soil properties within the sensor's zone of influence (Morgan et al 1999;Starr and Paltineanu 2002;Evett et al 2006). If care is taken in the installation of the access tubes, these potential problems can be limited; however, a soil-specific calibration is still required.…”
mentioning
confidence: 99%
“…The calibration showed significant differences even within the two medium soil textures, which only differ in bulk density. Morgan et al (1999) calibrated the EnviroScan probe to three sandy soils in Florida, USA with very satisfactory coefficients of determination (R 2 =0.83). They also compared their equation with the manufacturer default equation and concluded that the latter underestimates the soil water content in these soil types.…”
Section: Introductionmentioning
confidence: 98%
“…Specifically for the EnviroScan and the Diviner 2000, the manufacturer default equations derive from an average of three soil materials (sands, loams and clay loams) and provide relevant measurements of soil water content. The measurements resulting from these equations are inaccurate and often overestimate the soil water content (Leib et al, 2003;Starr and Paltineanu, 1998) or, in the case of light soil, underestimate it (Morgan et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation